Introduction to Community Psychology - Jason, Leonard A.; Glantsman, Olya; O'Brien, Jack F. (Open textbook library., 2019)
This textbook will show you how to comprehensively analyze, investigate, and address escalating problems of economic inequality, violence, substance abuse, homelessness, poverty, and racism. It will provide you with perspectives and tools to partner with community members and organizations to promote a fair and equitable allocation of resources and opportunities.